Feeling and Becoming Emotional: Approaches to Affectivity in Ancient Greece (Circe de clásicos y modernos, 2022)
The importance of the ‘affective turn’ in classical studies is well acknowledged, as it can be perceived through the many interdisciplinary works that have beenpublished in the area during these last decades. Taking into account the challenges and difficulties involving the historical analysis of feelings, this paper intends to account for the contributions that have been made in the last years on the study of emotions in Antiquity. By specially focusing on classical Greece, we seek to offer a wide theoretical framework that could be useful for those willing to embark in this promising field of academic research.
Keywords: emotions; Ancient Greece; affectivity; Greek literature; rhetoric